Persepsi Mahasiswa terhadap Aplikasi Chat GPT sebagai Media Komunikasi Digial(Studi Kasus Komunikasi Massa pada Mahasiswa IIQ Jakarta) - Awaliyah, Najwa Sabila; Mukarromah, Al (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to analyze students' perceptions of the use of the Chat GPT application as a digital communication medium among students of the Al-Qur'an Science Institute (IIQ) Jakarta. This background is based on the importance of communication in human life. Moreover, along with the development of technology, applications such as Chat GPT have made it easier for users, especially students, to complete their assignments or work.The method used in this study is descriptive qualitative, with the main data source in the form of direct written interviews, also through Google Forms involving 100 students from various faculties and departments at IIQ Jakarta. This study emphasizes the analysis of student perceptions of the benefits and effectiveness, and motivation in using Chat GPT, as well as individual values towards them, as students.The research methods used include collecting primary data through written interviews, as well as secondary data from relevant literature. Data analysis is carried out interactively through data reduction, data presentation, and drawing conclusions. This study uses the Dufuni innovation theory approach to analyze the stages of student benefits in adopting Chat GPT as a digital communication medium. The results of the study show that the majority of IIQ Jakarta students consider Chat GPT to make it easier for students to convey visual messages effectively. This conclusion provides important insights into the role of technology in individual life, as well as how Chat GPT can be a very helpful medium among students.